Current anesthesıa for Cesarean Sectıon - Erol, Demet Dogan; Aytac, Ismail (Clinical Journal of Obstetrics and Gynecology, 2018)
The choice of anesthesia for cesarean section should depend on the urgency of the procedure, in addition to the condition of the mother and fetus. It is widely accepted that regional anesthesia for cesarean section is preferable to general anesthesia. Regional techniques have several advantages. They lessen the risk of gastric aspiration, avoid the use of depressant anesthetic drugs and allow the mother to remain awake during delivery. The most common type of regional anesthesia for cesarean section is spinal anesthesia because of its simplicity, cost-effectiveness and speed of onset. It is suitable for cases of an emergent cesarean delivery. Hypotension during spinal anesthesia is a common that is associated with morbidity for both mother and fetus. Epidural anesthesia is preferred when physicians want to minimize the maternal hypotension or when intense motor blockage of the thoracoabdominal segments is not desired. General anesthesia still leads to a higher maternal mortality and should be reserved for absolute emergencies and cases where neuroaxial blockade is contraindicated.